Connecting to Compete 2018 : Trade Logistics in the Global Economy - Arvis, Jean-François; Ojala, Lauri; Wiederer, Christina; Shepherd, Ben; Raj, Anasuya; Dairabayeva, Karlygash; Kiiski, Tuomas (World Bank, Washington, DC, 2018)
This is the sixth edition of Connecting to Compete, a report summarizing the findings from the new dataset for the Logistics Performance Index (LPI) and its component indicators. The 2018 LPI also provides expanded data on supply chain performance and constraints in more than 100 countries, including information on time, distance and reliability, and ratings on domestic infrastructure quality, services, and border agencies. The 2018 LPI encapsulates the firsthand knowledge of movers of international trade. This information is relevant for policymakers and the private sector seeking to identify reform priorities for “soft” and “hard” trade and logistics infrastructure. Findings include: • Gaps in logistics performance between the bottom and top performers persist. • Supply chain reliability and service quality are strongly associated with logistics performance. • Infrastructure and trade facilitation initiatives still play an important role in assuring basic connectivity and access to gateways for most developing countries. • The logistics policy agenda continues to broaden, with growing focus on supply chain resilience, cyber security, environmental sustainability, and skills shortages.